Cohomologies and generalized derivations of n-Lie algebras - Atesli, Begum; Esen, Ogul; Sutlu, Serkan (Electronic Journals Project, 2022)
A cohomology theory associated to an n-Lie algebra and a represen-tation space of it is introduced. It is shown that this cohomology theory classifies generalized derivations of n-Lie algebras as 1-cocycles, and inner generalized derivations as 1-coboundaries.
Keywords: n-Lie algebra; Leibniz algebra; generalized derivation